Early Detection of Nasopharyngeal Carcinoma. (8th June 2011) - Tabuchi, Keiji; Nakayama, Masahiro; Nishimura, Bungo; Hayashi, Kentaro; Hara, Akira
Abstract : Nasopharyngeal carcinoma (NPC) is a unique disease with a clinical presentation, epidemiology, and histopathology differing from other squamous cell carcinomas of the head and neck. NPC is an Epstein-Barr virus-associated malignancy with a marked racial and geographic distribution. Specifically, it is highly prevalent in southern China, Southeast Asia, and the Middle East. To date, most NPC patients have been diagnosed in the advanced stage, but the treatment results for advanced NPC are not satisfactory. This paper provides a brief overview regarding NPC, with the focus on the early detection of initial and recurrent NPC lesions.